Attitudes of Primary Stage Teachers Towards the Use of Active Learning Methods in Teaching in Sahab Brigade Schools in Amman Governorate - Abbas, Weam Waleed (Journal of Educational and Psychological Sciences, 2023)
The study aimed to identify the attitudes of the primary stage teachers in Sahab Brigade schools in the Amman governorate towards the use of active learning methods in teaching, and for this purpose a questionnaire of (30) items was designed to measure the teachers’ attitudes towards the knowledge and awareness of these methods by the teachers, and regarding the importance reflected on the student. And The descriptive survey method was followed in applying the study and after verifying the validity and reliability of the tool, it was applied to (150) female teachers who were randomly selected from (3) government schools in the Sahab Brigade area in Amman governorate. In order to answer the study questions, the arithmetic averages and standard deviations of the responses of the parameters on the sub-domains and the total field of the questionnaire were extracted. Using methods), the averages and standard deviations were extracted for the content of the paragraphs and the results were discussed. In the light of the results of the study, appropriate recommendations were made regarding the need to include active learning within its educational curricula and methods, train and qualify teachers, and provide resources and infrastructure for that.